Students' Critical Thinking in Solving Geometry Problems Based on Honey & Mumford's Learning Styles - Miswanto, Miswanto; Muniri, Muniri (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
The purpose of this study is to describe students' critical thinking in solving geometry problems based on Honey & Mumford's learning styles. The research approach is a qualitative research with a descriptive exploratory research type. The subjects in this study were students of the Mathematics Education Department, Faculty of Tarbiyah and Teacher Training, UIN SATU Tulungagung, semester 1. First, the critical thinking of subjects in solving geometry problems based on the learning styles of activist and reflective groups is in the fairly critical category. Second, the critical thinking of subjects in solving geometry problems based on the reflective group learning style and category theory is quite critical. Third, the subject's critical thinking in solving geometry problems based on the learning styles of the theoretical and pragmatic groups in the critical category. Fourth, critical thinking of subjects in solving geometry problems based on the learning styles of the pragmatic and activist groups in the critical category.